Learning From Personality A.H. Nasution: Starting from Glory to Getting Out of the Political and Military Stage in Indonesia - Samudra Eka Cipta (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
General Abdul Haris Nasution is a national hero who has been educated from the military. Starting from being the Commander of the KNIL (Dutch East Indies Army) to becoming Minister of Internal Defense. Nasution once served as Commander of the Siliwangi Military Command. Nasution was very true of the military world. Nasution had been the target of murder from the PKI (Indonesian Communist Party). However, Nasution escaped death until he suffered minor injuries and legs. Nasution was also entrusted as Chair of the MPRS (Provisional People's Consultative Assembly). When Soekarno was confronted by Mahmilub (Extraordinary Court) by reading Pel-Nakwasara (Complementary Nakwasara) which contained about the pledoi for his defense efforts related to the G 30 S (September 30, 1965). Nasution, who was then chairman of the MPRS, refused the pledoi and immediately replaced Suharto as president. The New Order period lasted for 32 years Nasution's fate became increasingly tragic. Nasution was withdrawn from military service by Soeharto when it was proven in the Petition Objection 50 which was signed by several former generals and officers loyal to Sukarno to criticize Suharto's policies at that time. This researchs uses historical research methods, in this study aims to study more deeply about the figure of Abdul Haris Nasution began his career as a military until the end of the tragic as a retired soldier. The problem in this research is 1) How is the initial gait of A.H. Nasution? 2) How was Abdul Haris Nasution's role in defending Indonesia's independence 3) how Nasution's relationship with Sukarno and Suharto.